NEOCLASSICISM ARRIVES TO THE NATIONAL RURAL LIFE IN THE NINETEENTH CENTURY: THE MUNICIPAL PALACE OF SAN RAMON - Villalobos Cubero, Lissy Marcela (2014)
The text includes a study about the architecture with neoclassical influence in a rural area. This place is located on community named San Ramón of Alajuela, Costa Rica; between nineteenth and twentieth centuries. The object of investigation was to read the forms how the liberal ideology, politic-economic power, is represented through the arts, specifically on civil architecture, with the municipal building and the context that influenced it. For this investigation were consulted fundamentally: minutes of municipal archives; documentation of archive from local museum and other texts about theme.